How the Other Half Sees It: E-cigarette Advertising Exposure and Subsequent E-cigarette Use Among U.S. Young Adult Cigarette Smokers. Issue 3 (8th July 2022) - Chen-Sankey, Julia; Lopez, Michael; Elhabashy, Maryam; Broun, Aaron
Abstract: Introduction: E-cigarette advertising may benefit young adult cigarette smokers in transitioning to using e-cigarettes. We assessed whether e-cigarette advertising exposure was associated with subsequent e-cigarette use among young adult cigarette smokers. Aims and Methods: Data were from Waves 4 (2016–2018) and 5 (2018–2019) of the nationally representative Population Assessment of Tobacco and Health (PATH) study adult survey. Respondents were young adult established cigarette smokers at Wave 4 (18–34 years; n = 3391) and a subsample of those who tried to quit smoking cigarettes completely in the past year at Wave 5 ( n = 1235). Multivariable logistic regressions were used to examine the associations between e-cigarette advertising exposure (by channel of exposure) and subsequent past-year e-cigarette use in general and e-cigarette use to quit smoking cigarettes, controlling for covariates. Results: At Wave 5, 43.4% of smokers reported past-year use of e-cigarettes; and 14.8% of smokers who tried to completely quit smoking reported past-year use of e-cigarettes to quit. E-cigarette advertising exposure was associated with subsequent past-year e-cigarette use (adjusted odds ratio [AOR] = 1.53, p < .0001, 95% confidence interval [CI] = 1.27, 1.86) and past-year use to quit smoking cigarettes (AOR = 1.65, p < .01, 95% CI = 1.19, 2.29). Advertising exposure through brick-and-mortar stores or websites/social media was similarly associated with both e-cigarette use behaviors. Discussion: Exposure to e-cigarette advertising among U.S. young adult established cigarette smokers may be associated with subsequent e-cigarette use and use to quit smoking. More research is needed to understand the features of e-cigarette advertising (eg, discounts, flavors, smoker-targeted claims) that may shape perception and behavior related to e-cigarette use among young adult smokers. Implications: Little is known about the associations between e-cigarette advertising exposure and e-cigarette use among young adult cigarette smokers who may benefit from switching to e-cigarettes. This study found that e-cigarette advertising exposure was positively associated with (1) subsequent e-cigarette use among U.S. young adult established cigarette smokers and (2) subsequent e-cigarette use to quit smoking cigarettes among those who tried to completely quit in the past year. These observed associations were driven by smokers who did not currently use e-cigarettes at baseline. E-cigarette advertising exposure through brick-and-mortar stores or websites/social media was also positively associated with subsequent e-cigarette use behaviors.